Pengetahuan Gizi dan Kejadian Stunting di SMP Negeri 9 Kota Jambi - Wulansari, Arnati; lazamza, taffana ummadithya; fadila, rara nurmala (Jurnal Akademika Baiturrahim Jambi, 2025)
Stunted children are a widely accepted predictor of poor quality human resources. Based on the results of the 2018 Riskesdas, the prevalence of stunting in Indonesia is 30.8%, with the prevalence of stunting in adolescents in the 13-15 year group, the nutritional status of very short adolescents is 12.9%, while the number of stunted adolescents is 21.7%. The results of the 2013 Riskesdas showed that the prevalence of stunting in adolescents aged 13-15 years and 16-18 years was 35.1% and 31.4%, respectively. To overcome the problem of stunting, it is necessary to know the factors that cause stunting. One of them is adolescent knowledge of nutrition. The general objective of this study was to determine the relationship between nutritional knowledge and the incidence of stunting in adolescents at SMP N 9 Jambi City. The research design used a cross-sectional study design. This research will be carried out in May - June 2023 at SMP N 9 Jambi City. Based on the research results, it was found that 75.0% of respondents had poor knowledge, and 9.1% experienced stunting. There is no relationship between knowledge about stunting and the incidence of stunting (P-value > 0.05).